PERAN PENYIDIK DALAM PENERAPAN DIVERSI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA DI WILAYAH POLRESTA SAMARINDA - SYANTRI SURYA ZAHID AFIF (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT       In national law the special protection of children in conflict with the law also stipulated in the Child Protection Act 23 of 2002 and Act No. 3 of 1997 on Juvenile Justice. However, in practice there are still many issues that arise, especially in the case of children in conflict with the law. Therefore, one solution that can be used is with the implementation of diversion (diversion) or with restorative justice, where the police are the frontline in its implementation.These researchers using research methods normative and juridical sociological. The data used are primary data obtained from field studies and secondary data from literature. A field study conducted by interview, The results of the study, that the implementation of diversion based on the poor handling of the children in conflict with the law and the best interests of the child based on the International Rules and National Regulations, such as Law No. 2 In 2002, TR Kabareskrim and Agreements 5 (five) and Police departments.In the implementation of diversion investigator plays an important role, one of which is a major gateway entry of pediatric cases. But the implementation is found several barriers such as lack of socialization regarding the diversion of good to the investigator, the public and other relevant institutions. So that the implementation is less effective. Besides, the rules are also not able to guarantee the implementation of the diversion.In that respect the advice that can be given include the implementation of a thorough socialization at all levels within the police without exception and related parties, as well as clarifying and strengthening the implementation of the diversion in a government regulation.Keywords: Investigator, Diversion, Children in Conflict with the Law